Thiadiazoloquinoxaline-Based Semiconducting Polymer Nanoparticles for NIR-II Fluorescence Imaging-Guided Photothermal Therapy - Gu, Xuxuan; Liao, Keyue; Lu, Xiaomei; Huang, Wei; Fan, Quli (Frontiers in Bioengineering and Biotechnology, 2021)
Phototheranostics have gained more and more attention in the field of cancer diagnosis and therapy. Among variety of fluorophores for phototheranostics, semiconducting polymer nanoparticles (SPNs), which usually constructed by encapsulating hydrophobic semiconducting polymers (SPs) with amphiphilic copolymers, have shown great promise. As second near-infrared (NIR-II) fluorescence imaging has both higher imaging resolution and deeper tissue penetration compared with first near-infrared (NIR-I) fluorescence imaging, NIR-II fluorescent SPNs have been widely designed and prepared. Among numerous structural units for semiconducting polymers (SPs) synthesis, thiadiazoloquinoxaline (TQ) has been proved as an efficient electron acceptor unit for constructing NIR-II fluorescent SPs by reacting with proper electron donor units. Herein, we summarize recent advances in TQ-based SPNs for NIR-II fluorescence imaging-guided cancer photothermal therapy. The preparation of TQ-based SPNs is first described. NIR-II fluorescence imaging-based and multimodal imaging-based phototheranostics are sequentially discussed. At last, the conclusion and future perspectives of this field are presented.